Utilisation d’un SIG pour l’évaluation et la cartographie des risques d’érosion hydrique par l’Equation Universelle des Pertes en sol Révisée (RUSLE) dans le Département de Saraya (Sénégal) - René Boissy; Mamadou Ndiaye; Moise Diatta; Maguette Mbaye (VertigO)
The department of Saraya has been confronted with erosion for the last two decades. Despite the anti-erosion strategies (dykes, stone barriers, hedgerows, bunds, trenches, regeneration of vegetation cover, mulching) put in place by the local people and the local authorities, erosion is becoming increasingly worrying in this locality. This natural hazard constitutes a major environmental problem and threatens economic activities. This study assessed the potential risk of erosion by modelling the factors R, K, LS, C and P. The integration of the model into a Geographic information system (GIS) facilitated the elaboration of thematic maps (topography, rainfall erosivity, soil erodibility and land use) to assess the risk of erosion and to map the vulnerable areas and those less sensitive to this hazard. Coupling the GIS with the revised universal soil loss equation allowed the estimation of the impacts of groundwater runoff. Soil losses range from 0.01 t/ha/yr to 134.64 t/ha/yr, with an average of 33,46 t/ha/yr and a standard deviation of 57.29. The GIS/RUSLE approach helps decision-makers and planners to develop scenarios of soil degradation and to plan anti-erosion strategies in areas where erosion is predominant.